European constitutionalism beyond the state - Weiler, Joseph, 1951-; Wind, Marlene, 1963- (Cambridge University Press, 2003)
Leading scholars of European constitutionalism highlight different facets of the new constitutional discussion. This book delineates new ways of thinking about the future of Europe. This book will appeal to anyone interested in the timely subject of constitutionalism including students and practitioners of law, politics and philosophy.